Intersectionality as emergence. - Jorba, Marta; López de Sa, Dan (Philosophical Studies, 2024)
Intersectionality is the notion that concerns the complexity of the experiences of individuals in virtue of their belonging to multiple socially significant categories. One of its main insights is that the way society is structured around categories such as gender, race, sexuality, class, etc., produces distinctive and specific forms of discrimination and privilege for groups in the intersections. In this paper, we suggest conceiving intersectionality as a general metaphysical framework wherein specific claims to the effect that the experiences of discrimination of Black women, among others, can be fruitfully formulated and examined. The main claim is that intersectional experiences emerge from the conjunction of social categories when social structures make them relevant vis-à-vis discrimination and privilege. We then argue that our view has three main virtues: metaphysical neutrality, explanatory flexibility and methodological openness. Explaining these virtues will allow us to contrast our proposal with alternatives from the recent literature.